Porting LabVIEW to an ARM9 microcontroller - Nguyen, Ho Nam. (2009)
Science fiction movies often depict a future where the world is fully automated from housing to transportation to personal devices and so on. Will that future come true? How is it going to happen? One possibility is the total integration of embedded systems into human life. In fact, embedded applications can be found everywhere: in cars, at homes, in hand phones. Nowadays, engineers are more likely to encounter problems which require solutions in embedded form. Due to the increasing complexity of embedded programs, programming embedded application proves to be a significant burden for domain experts. To leverage domain experts, National Instruments, a leader in providing measurement and automation tools, offers intuitive graphical programming for embedded application development. By using Microprocessor SDK module, engineers can port LabVIEW graphical programming language to any 32-bit microprocessor. This project aims to port LabVIEW to an ARM9 microcontroller to demonstrate the viability of LabVIEW to be an integrated and intuitive graphical development platform for embedded application. In order to implement the porting process, Microprocessor SDK and ARM9 microcontroller were learned and researched. The major sources of information were software and hardware manuals, tutorials on website, online discussion forum, provided examples and interaction with National Instruments embedded expert. With decent understanding of LabVIEW embedded modules and ARM9 microcontroller, the porting process was started. Various problems were encountered. However, with perseverance as well as support from supervisors and National Instruments, the porting process was implemented successful. By the end of the project, embedded applications for the ARM9 microcontroller – MCBSTR9 were developed easily in LabVIEW graphical programming environment with features such as comprehensive set of basic programming elements, advanced math and analysis functions, simple drag-and-drop I/O operation (Elemental I/O), and integrated application building and downloading. Demos were created to showcase embedded programming in LabVIEW and benefits. Finally, this report was written to report the whole project and to provide a clear and holistic view of the complicated process of porting LabVIEW to an ARM microcontroller. A compact porting guideline was written, with hands-on experience learned from the project, to be a reference for future LabVIEW porting projects.